KEINGINAN PINDAH KERJA TENAGA KESEHATAN PADA MASA PANDEMI COVID-19 DITINJAU DARI FAKTOR BAHAYA PSIKOSOSIAL DI TEMPAT KERJA DAN SINDROM BURNOUT - Felicia Felicia (The Asia Pacific Journal Of Management Studies, 2021)
Health workers are vulnerable to psychosocial hazards and experience burnout syndrome, especially during a pandemic. Both of these things can cause a person to have a desire to change jobs. High turnover rates, especially in areas of work that lack manpower, such as in the health sector, will be a direct or indirect economic problem. This study aims to determine the effect of psychosocial hazards and burnout syndrome on the desire to change jobs in health workers in hospitals. The research uses a non-experimental quantitative approach with primary data from health workers taken using the convenient sampling technique at a hospital in the municipality of Central Jakarta, Indonesia, from March 2021 to May 2021. The data obtained will be analyzed using descriptive and inferential statistics using PLS. -SEM. The results showed that psychosocial hazards and burnout syndrome had a positive effect on the desire to change jobs for health workers.